Tracing an ancestral mutation: genealogical and haplotype analysis of the infantile onset spinocerebellar ataxia locus. - Varilo, T; Nikali, K; Suomalainen, A; Lönnqvist, T; Peltonen, L (Genome Research, 1996)
Infantile onset spinocerebellar ataxia (IOSCA) is a progressive neurological syndrome exhibiting an autosomal recessive pattern of inheritance. The characteristic features were described in Finland in the beginning of 1990s. Having shown that IOSCA does not segregate with any of the markers linked to other hereditary ataxias and thus represents a genetically distinct disease, we assigned the locus of this new hereditary ataxia to 10q23.3-q24.1. To approximate the age of the Finnish IOSCA mutation and to investigate the possible existence of more than one mutation underlying the disease, the ancestors of 13 IOSCA families were identified by use of church records dating back to the 1500s. The IOSCA pedigrees were frequently merged, providing support for these having one common ancestor. Analysis of the extended IOSCA haplotypes exposed ancient recombination events and revealed one core haplotype of four markers on a region of approximately 2 cM, which was unequivocally present in 92% of disease chromosomes. Both genealogical and haplotype data thus suggest that a single IOSCA ancestral mutation was introduced into the Finnish population most probably approximately 30-40 generations ago before the time when the general east-west migration took place within Finland.